Analisis Kriptografi Algoritma Blowfish pada Keamanan Data menggunakan Dart - Yoga Pratama; Tata Sutabri (LPPM STT Terpadu Nurul Fikri, 2023)
Data security is a vital aspect of information technology to maintain the integrity and authenticity of data from unauthorized access. In supporting this, an approach is taken to protect sensitive information and data. In this research, cryptographic techniques were analyzed and tested to secure data in text, which is commonly used as a password using the Blowfish cryptographic algorithm. The goal is to determine how strong, secure, and fast the blowfish algorithm maintains and executes the text data encoding. The research method used is an in-depth theoretical analysis followed by computational experiments using dart programming. Based on the study and testing carried out, the results of this research show that the use of cryptographic techniques with the blowfish algorithm on text data samples can be used as an alternative for securing data. The results show that the blowfish algorithm pattern has security because it uses various techniques to change and present data, supported by an execution time of less than 10 seconds and minimal memory usage of under 5 MB. Therefore, the blowfish algorithm can be used as a cryptographic choice in developing robust and fast text-based data security.